Open fractures in pre-salt silicified carbonate reservoirs in block BM-C-33, the Outer Campos Basin, offshore Brazil. Issue 4 (2021) - Wennberg, O. P.; McQueen, G.; Luca, P. H. Vieira de; Lapponi, F.; Hunt, D.; Chandler, A. S.; Waldum, A.; Camargo, G. Nery; Castro, E.; Loures, L.
No abstract available